2020
DOI: 10.1038/s41591-019-0716-8
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of crizotinib in lung cancers harboring a MET exon 14 alteration

Abstract: MET exon 14 alterations are oncogenic drivers of non-small cell lung cancers (NSCLCs). 1These alterations are associated with increased MET activity and preclinical sensitivity to MET Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:http://www.nature.com/authors/editorial_policies/license.html#terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
260
4
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 296 publications
(277 citation statements)
references
References 45 publications
8
260
4
5
Order By: Relevance
“…In an analysis of 148 patients harboring the METex14 mutation, 63% of the cohort's NSCLCs expressed PD-L1: 1-49% for 22% and >50% for 41%. 100 Their median tumor mutation burden was 3.8 mutations/megabase, lower than that of a control historical cohort, whose tumors did not carry the METex14 mutation (5.7 mutation/megabase: P<0.001).…”
Section: Immunotherapy For Patients With a Met-pathway-signaling Abnomentioning
confidence: 75%
See 1 more Smart Citation
“…In an analysis of 148 patients harboring the METex14 mutation, 63% of the cohort's NSCLCs expressed PD-L1: 1-49% for 22% and >50% for 41%. 100 Their median tumor mutation burden was 3.8 mutations/megabase, lower than that of a control historical cohort, whose tumors did not carry the METex14 mutation (5.7 mutation/megabase: P<0.001).…”
Section: Immunotherapy For Patients With a Met-pathway-signaling Abnomentioning
confidence: 75%
“…73,98,99 Updated results from the PROFILE-1001 study, in which 69 treatment-naïve or chemotherapy-refractory, METex14+ NSCLC patients participated, showed three complete responses and 18 partial responses (ORR, 32% [95% CI: 21-45]) with median PFS at 7.3 [95% CI: 5.4-9.1] months. 100 In the METRO study, which included 26 crizotinibtreated patients (16 with MET amplification, nine harboring the METex14 mutation and one with concurrent abnormalities), the ORR was 20% for patients with METex14 mutations, with median PFS at 2.6 [95% CI: 2.2-3.0] months and median OS at 3.8 months [95% CI: 1.7 -5.8]. No difference between MET-amplified and METex14-mutated patients was found for any clinical endpoint.…”
Section: Evaluation Of Anti-met Agents In Patients With Nsclcs Harbormentioning
confidence: 99%
“…37 Numerous MET-targeting agents currently are in early-phase trials, including TKIs, antibodies, bispecific antibodies, and drug-antibody conjugates (Table 1). 32,34,36,[38][39][40][41][42][43] Attempts have been made to combine TKIs with ICIs for the treatment of NSCLC. Toxicity was shown to be the most important limitation; to the best of our knowledge, no signal for synergy has clearly emerged to date.…”
Section: Targeting Metmentioning
confidence: 99%
“…Recently, case studies and early‐phase trials in MET ex14‐mutated NSCLC have demonstrated durable responses to multitarget TKIs, such as crizotinib and cabozantinib [11–13], as well as MET‐selective TKIs, such as tepotinib and capmatinib [14–16]. MET TKIs may also improve overall survival in patients with MET ex14 mutations [17].…”
Section: Molecular Tumor Boardmentioning
confidence: 99%